Skills and Employability in Mozambique : Implications for Education and Training Policies - Cho, Yoonyoung; Feda, Kebede (World Bank, Washington, DC, 2015)
Mozambique is experiencing significant population growth with a growing number of youth (ages 15-34) into the labor market. The surge of the raw number of individuals, particularly young people, opens both challenges and opportunities: challenges, because of the need to create sufficient jobs to employ new entrants; opportunities, because if well managed, the country will benefit from a young, dynamic labor market where innovations and creative activities serve as an engine of growth, driving up per capita income and standards of living. The paper is organized as follows. The first two sections describe the supply and demand side diagnostics of the labor market, respectively, by analyzing the profiles of workers and by examining where jobs are being created. The next section discusses the determinants of employment, type of work, and earnings. Based on this analysis of the trends and labor market outcomes, the last section identifies and discusses key areas of policy interventions.